Social choice and welfare - Pattanaik, Prasanta K.; Salles, Maurice (Contributions to economic analysis, 1983)
This volume comprises papers presented at the Symposium on Collective Choice, by leading experts in this field. It presents recent advances in Social Choice Theory and Welfare Economics. The papers are classified in two broad groups: (1) those dealing with the ethical aspects of the theory of social choice and (2) those concerned with the positive aspects. The papers in the first part are concerned with the Arrow-type aggregation problem or aspects of it and with more specific questions relating to optimality, justice and welfare. In part II several papers discuss the problem of strategic misre.